2021
DOI: 10.32530/jaast.v5i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Performance of Aromatic Fine Rice as Influenced by Varieties and Fertilizer Managements

Abstract: This Research was conducted to investigate the effect of fertilizer management on growth and yield performance of aromatic fine rice varieties. The experiment consisted of two factors were aromatic fine rice and fertilizer management. There were four varieties namely Kalizira, Kataribhog, Tulshimala and BRRI Dhan34 with four fertilizer treatments recommended dose of fertilizers (T1), cowdung @ 10 tha-1 (T2), 50% of recommended dose of fertilizers + 50% cowdung(T3), 75% of recommended dose of fertilizers + 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The variation in plant height among the varieties was probably due to heredity or varietal characters. Similar results were reported elsewhere (Kirttania et al, 2013;Ray et al, 2015;Islam et al, 2021). Plant height was significantly influenced by nutrient management irrespective of growth stages.…”
Section: Plant Heightsupporting
confidence: 91%
“…The variation in plant height among the varieties was probably due to heredity or varietal characters. Similar results were reported elsewhere (Kirttania et al, 2013;Ray et al, 2015;Islam et al, 2021). Plant height was significantly influenced by nutrient management irrespective of growth stages.…”
Section: Plant Heightsupporting
confidence: 91%
“…However, considering nutrient management the highest 1000-grain weight (12.54 gm) was found with 75% of RDF + poultry manure @ 2.5 t ha -1 and the lowest 1000-grain weight (10.74 gm) was obtained from control treatment (Table 3). In a similar study, Teli et al (2018); Mahata et al (2019) and Islam et al (2021b) found that, various combinations of organic manures and inorganic fertilizers had a significant effect on the 1000-grain weight of rice. Considering the interaction between seedling age and nutrient management, results revealed that, the highest 1000-grain weight (13.76 gm) was recorded from 30 days old seedling along with 75% of RDF + poultry manure @ 2.5 t ha -1 and the lowest 1000-grain weight (10.26 gm) was obtained from 60 days old seedling along with no manures and fertilizers (Table 4).…”
Section: Number Of Grains Panicle -1mentioning
confidence: 86%
“…Also, the highest harvest index (43.03%) was found in 75% of RDF + poultry manure @ 2.5 t ha -1 and the lowest harvest index (41.60%) was obtained from treatment 50% of RDF + Cow-dung @ 5 t ha -1 (Table 3). Teli et al (2018);and Islam et al (2021b) stated that, the harvest index is significantly influenced by nutrient management. Also, Roy et al (2017) showed that, harvest index was significantly influenced by fertilizer management.…”
Section: Harvest Indexmentioning
confidence: 99%